An efficient reliability-based design of TMD & MTMD in nonlinear structures under uncertainty. (May 2023) - Shamsaddinlou, Amir; Shirgir, Sina; Hadidi, Ali; Farahmand Azar, Bahman
Abstract: One of the methods to improve the performance of tuned mass dampers is to combine the primary and auxiliary mass dampers in series, known as multiple tuned mass dampers. The mechanical properties of these dampers influence the seismic behavior of structures equipped with tuned mass dampers. Generally, the determination of TMD parameters to achieve optimal seismic behavior is defined in the framework of optimization problems. In structures with nonlinear behavior, there are several sources of uncertainty in the structure, which emphasizes the importance of using the reliability-based design optimization method. For this purpose, two strategies based on the meta-heuristic optimization and reliability-based design optimization method are used for the optimal design of TMD and MTMD. In the RBDO method, the optimal design is performed based on the objective function established on the target reliability of the structure. Furthermore, a hybrid metaheuristic method was developed based on BOA and CSS algorithms to increase search-ability. The results show the efficiency of the HBC algorithm in solving engineering design problems. Also, reliability analysis and sensitivity analysis are conducted on passive controlled structures to display the effect of uncertainty in mechanical parameters of the system and their importance in the reliability of the system. Also, the optimum design of TMD and MTMD was evaluated based on the target reliability using the efficient RBDO method. The results show that the RBDO strategy has an excellent ability to design TMD and MTMD with a good performance in reducing seismic responses.